Towards understanding cell penetration by stapled peptides. Issue 1 (14th October 2014) - Chu, Qian; Moellering, Raymond E.; Hilinski, Gerard J.; Kim, Young-Woo; Grossmann, Tom N.; Yeh, Johannes T.-H.; Verdine, Gregory L.
Abstract : A systematic study on cell penetration by stapled peptides. Abstract : Hydrocarbon-stapled α-helical peptides are a new class of targeting molecules capable of penetrating cells and engaging intracellular targets formerly considered intractable. This technology has been applied to the development of cell-permeable ligands targeting key intracellular protein–protein interactions. However, the properties governing cell penetration of hydrocarbon-stapled peptides have not yet been rigorously investigated. Herein we report our studies to systematically probe cellular uptake of stapled peptides. We developed a high-throughput epifluorescence microscopy assay to quantitatively measure stapled peptide intracellular accumulation and demonstrated that this assay yielded highly reproducible results. Using this assay, we analyzed more than 200 peptides with various sequences, staple positions and types, and found that cell penetration ability is strongly related to staple type and formal charge, whereas other physicochemical parameters do not appear to have a significant effect. We next investigated the mechanism(s) involved in stapled peptide internalization and have demonstrated that stapled peptides penetrate cells through a clathrin- and caveolin-independent endocytosis pathway that involves, in part, sulfated cell surface proteoglycans, but that also seems to exploit a novel, uncharacterized pathway. Taken together, staple type and charge are the key physical properties in determining the cell penetration ability of stapled peptides, and anionic cell surface proteoglycans might serve as receptors to mediate stapled peptide internalization. These findings improve our understanding of stapled peptides as chemical probes and potential targeted therapeutics, and provide useful guidelines for the design of next-generation stapled peptides with enhanced cell permeability.